Exposure to air pollution during pregnancy and newborn liver function. (July 2019) - Pejhan, Akbar; Agah, Jila; Adli, Abolfazl; Mehrabadi, Saide; Raoufinia, Ramin; Mokamel, Adel; Abroudi, Mina; Ghalenovi, Mina; Sadeghi, Zahra; Bolghanabadi, Zahra; Bazghandi, Malihe Sadat; Hamidnia, Masoud; et al.
Abstract: Exposure to air pollution has been associated with a wide range of adverse health outcomes. However, the available evidence on the impact of air pollution exposures on liver enzymes is still scarce. The aim of the present study was to assess the relationship between exposure to ambient PM1, PM2.5 and PM10 during pregnancy and serum level of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) and gamma-glutamyl transferase (GGT) in cord blood samples of newborns. Moreover, the association between total street length in different buffers and distance to major roads at the maternal residential address and liver enzymes were investigated. This cross-sectional study was based on data from a sample of 150 newborns, from Sabzevar, Iran. Land use regression models were used to estimate concentrations of air pollutants at home during pregnancy. Multiple linear regression was developed to estimate association of AST, ALT, ALP and GGT with air pollution controlled for relevant covariates. In fully adjusted models, increase in PM1 and PM2.5 as well as PM10 were associated with higher levels of AST, ALT and GGT. Moreover, there was a significant association between total street length in a 100 m buffer at residential address with AST, ALT and GGT. Each meter increase in distance to major roads was associated with −0.017 (95% confidence interval (CI): -0.028, −0.006) decrease in AST. Overall, our findings were supportive for association between PMs exposure during pregnancy and increase in liver enzymes in newborns. Further studies are needed to confirm these findings in other settings and populations. Highlights: Maternal exposure to PMs and change in fetal liver enzymes were investigated. LUR models were applied to estimate PM1, PM2.5 and PM10 at residential address. Increase in PM1, PM2.5 and PM10 was associated with higher level of AST, ALT and GGT.